Mathcad a tool for engineering problem solving - Pritchard, Philip J. (McGraw-Hill Higher Education, 2008)
(Basic Engineering Series and Tools) consists of modularized textbooks offering virtually every topic and specialty likely to be covered in an introductory engineering course. All the texts boast distinguished authors and the most current content. These inexpensive B.E.S.T. modules are easily combined with each other to construct the ideal Intro to Engineering course. The goal of this series is to provide the educational community with material that is timely, affordable, of high quality, and flexible in how it is used.